Composição isotópica – δ18o e δd – das águas do sistema aquífero bauru no estado de são paulo - Stradioto, Marcia Regina [UNESP]; Chang, Hung Kiang [UNESP] (My University, 2015)
Environmental isotopes, particularly d18O e dD, provide important information on groundwater origin, mixture of different groundwater and aquifer recharge. The present study presents the results of isotope ratio of d18O e de dD for groundwater of Bauru Aquifer System (SAB), as well as their distribution over the aquifer units occurring in the state of São Paulo. The study was performed using water samples collected in previously selected wells in the outcrop areas of the Bauru Group in São Paulo. Statistical analysis was useful to test isotope ratios similarities among the major aquifer units, using 339 groundwater samples distributed over the entire area of occurrence of SAB in the state of São Paulo. Isotope ratios vary from –8,94‰ to –3,55‰ for d18O and from –62,5‰ to –25,4‰ for dD with the values falling closely along the Global Meteoric Water Line.
Isotopic composition - δ18O and δD - of the Bauru Aquifer Water System in the State of São Paulo